2013
DOI: 10.1002/jip.1395
|View full text |Cite
|
Sign up to set email alerts
|

Linking Crimes Using Behavioural Clues: Current Levels of Linking Accuracy and Strategies for Moving Forward

Abstract: The number of published studies examining crime linkage analysis has grown rapidly over the last decade, to the point where a special issue of this journal has recently been dedicated to the topic. Many of these studies have used a particular measure (the area under the receiver operating characteristic curve, or the AUC) to quantify the degree to which it is possible to link crimes. This article reviews studies that have utilised the AUC and examines how good we are currently at linking crimes (within the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 54 publications
1
47
0
1
Order By: Relevance
“…Woodhams et al, 2007). A number of studies have found evidence for the assumptions of crime linkage in serial crime (for a review of the research to date on behavioural crime linkage, see Bennell et al, 2014). While serial homicide has been studied less than, for example, rape, a few studies have found serial homicide offenders to be somewhat consistent in their behaviour over the course of their series (Bateman and Salfati, 2007;Salfati and Bateman, 2005;Salfati et al, 2015;Santtila et al, 2008;Sorochinski and Salfati, 2010).…”
Section: Behavioural Crime Linkingmentioning
confidence: 99%
“…Woodhams et al, 2007). A number of studies have found evidence for the assumptions of crime linkage in serial crime (for a review of the research to date on behavioural crime linkage, see Bennell et al, 2014). While serial homicide has been studied less than, for example, rape, a few studies have found serial homicide offenders to be somewhat consistent in their behaviour over the course of their series (Bateman and Salfati, 2007;Salfati and Bateman, 2005;Salfati et al, 2015;Santtila et al, 2008;Sorochinski and Salfati, 2010).…”
Section: Behavioural Crime Linkingmentioning
confidence: 99%
“…Third, inter‐crime distance and temporal proximity were not included in the current variables, although these parameters have been associated with large AUC values in many linking studies of other types of crimes (cf. Bennell et al ., ). As Bennell et al () indicated, research examining the potential value of spatial and temporal variables in cases of sexual assault is lacking because the sample size of these studies is small, and crimes to be analyzed must be much more geographically and temporally dispersed than in analyses of other types of high‐volume property crimes.…”
Section: Discussionmentioning
confidence: 97%
“…Bennell et al ., ). As Bennell et al () indicated, research examining the potential value of spatial and temporal variables in cases of sexual assault is lacking because the sample size of these studies is small, and crimes to be analyzed must be much more geographically and temporally dispersed than in analyses of other types of high‐volume property crimes. The current study also excluded spatial and temporal variables, because it appeared obvious that linking crimes based on inter‐crime distance and temporal proximity would be highly accurate in the current sample; the sample consisted of incidents from a wide area (throughout Japan) over a number of years (over a decade).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations